BROWN SPOT CAUSED BY CURVULARIA SPP., A NEW DISEASE OF ASPARAGUS - B. SALLEH B. SALLEH; A. SAFINAT; L. JULIA; C.H. TEO (BIOTROPIA, 1996)
The distribution, aetiology and symptomatology of a new disease on asparagus ferns, which we have termed brown spot, is described. Descriptions of and a key to identification of the causal organisms, Curvularia brachyspora, C. eragrostidis, C. lunata and C. pallescens, are also presented. Pathogenicity tests showed that C. lunata was the dominant and most virulent of the four species. Inoculation with conidial suspensions or mycelial transfers through wounded ferns were more effective in inducing the disease than inoculations on unwounded ferns. This is the first record of C. brachyspora in Malaysia and the first report of this disease on asparagus Key words: Malaysia/Plant diseases/Brown spotJCurvularia brachyspora/Curvularia eragrostidts/Curvularialunata/Curvularia pallescens/Asparagus.